Comportamento à compressão de estacas escavadas de pequeno diâmetro em campo experimental na cidade de Cruz Alta/RS - Masutti, Gustavo Corbellini (2020)
In this work, the behavior of short and small diameter excavated piles submitted to tests of static load to compression, performed in an experimental field in the city of Cruz Alta / RS, is evaluated. At the research site, simple recognition tests (SPT) were performed, collections of deformed samples from the A and B horizons of the soil for characterization tests, particle size and physical indexes. Nine piles were excavated by a mechanical auger with a length of 3.00 m, diameter of 0.30 m and different construction characteristics: three piles concreted according to the usual practice, resisting by lateral and tip friction; three floating piles, having only resistance by lateral friction, executed with expanded polystyrene discs at the tip that were later dissolved, and three piles with improved tip resistance by including a layer of compacted crushed stone at the bottom of the drilling. The results of the load versus settlement curves obtained in the load tests were interpreted by the method of NBR 6122 (ABNT, 2019) and by the method of Van der Veen (1953), for later comparison with the values estimated by established semi-empirical methods of calculation load capacity. The results showed that the piles have a low breaking load capacity, with conventional piles having the greatest variations. The floating piles reached load capacity values similar to conventional piles, demonstrating the influence of lateral friction resistance in the soil in question. Piles with an improved tip reached, on average, loads 18.9% higher than conventional piles. They also presented homogenization of the settlements and / or their behavior when loaded. Due to its ease of execution, it becomes a simple, affordable and efficient alternative for obtaining an increase in short pile resistance. For the prediction of load capacity through correlations with simple recognition tests (SPT), the method of Décourt and Quaresma (1978) showed values 23.7% higher than the average values found in load tests. When compared with the average of the results of floating piles, the value related to the load capacity by lateral friction was 4.6% lower. The presented study demonstrates the importance of carrying out load tests on piles to verify in loco the loads obtained from traditional calculation methods.